A intensificação da agricultura e o papel de árvores isoladas na conservação da fauna de formigas do cerrado fora de unidades de conservação - Frizzo, Tiago Luiz Massochini (2011)
The destruction of natural habitats and the intensification of agriculture are considered the major threats to biodiversity conservation. Given the rapid expansion of agricultural frontiers in the areas of native vegetation in the Cerrado, it is imperative to know the capacity of conservation of the native fauna in agroecosystems. Thus, this study aims to determine how much of the natural biodiversity of ants is maintained in agroecosystems in the Cerrado region (a savanna biome), as well as determine whether the presence of trees in these agroecosystems adds some value to conservation of the ant fauna. Samples were collected in the city of Uberlândia (MG) and Campo Alegre de Goiás (GO) in two soybean fields and four pastures where there was a presence of isolated trees (Caryocar brasiliensis; popularly known as Pequizeiro) were present. Pitfall traps were placed in the tree crowns, on the soil surface and in the underground. To evaluateif the presence of trees increased the species richness at ground level, ground and underground traps were placed just below the tree crown and 30 meters away from any tree (deemed to be outside the influence of trees). In total more than 200,000 ants, distributed in 204 species, were collected. The presence of isolated trees significantly increased species richness regardless of the type of agroecosystem. This increase in richness was due primarily to an increase of arboreal species, although an increase in the number of species that forage and nest in the soil was also detected. The results also suggest that the intensification of agriculture has negative effects on the ant fauna. This is because pasture areas (which gradually are being replaced by monocultures, such as soybean plantations) have a more diverse ant fauna and a fauna more similar to that found in the native cerrado vegetation, than the soybean fields. Moreover, the presence of isolated trees (which caused an increase in local ant species richness) is much less frequent in soybean fields than in pastures. Overall, these results suggest that the maintenance of isolated trees and the adoption of other measures that increase the species richness of ants, not only improve the conservation value of agricultural lands but also may help to maintain the ecological services provided by this important insect group.